1983
DOI: 10.1128/iai.39.1.91-99.1983
|View full text |Cite
|
Sign up to set email alerts
|

Serological analysis of the subgroup protein of rotavirus, using monoclonal antibodies

Abstract: Ten monoclones directed to the 42,000-dalton inner structural protein of rotavirus were analyzed. Eight monoclones reacted broadly with antigenic domains common to virtually all mammalian rotaviruses. Two monoclones had specificities similar or identical to previously characterized subgroup specificities. These subgroup monoclones were more efficient in detecting subgroup antigen than either hyperimmune or postinfection antisera. Using the subgroup monoclones, we determined that some animal as well as human ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
180
0
4

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(190 citation statements)
references
References 30 publications
6
180
0
4
Order By: Relevance
“…It consists of 397 residues that are highly conserved among group A rotavirus strains. VP6 determines the group and subgroup antigenic specificities of the virus [80]. The protein has a welldefined 3D structure (PDB ID: 1QHD) {Fig.…”
Section: Structural Protein Vp6mentioning
confidence: 99%
“…It consists of 397 residues that are highly conserved among group A rotavirus strains. VP6 determines the group and subgroup antigenic specificities of the virus [80]. The protein has a welldefined 3D structure (PDB ID: 1QHD) {Fig.…”
Section: Structural Protein Vp6mentioning
confidence: 99%
“…MAb technology has been applied to most of the major pathogens that cause scours in neonatal calves, piglets and lambs. Greenberg et al (1983) demonstrated that MAbs against the 42kDa major structural protein of rotavirus could be used for preliminary serotyping of strains from different animal species, and Sabara et al (1985) used MAbs to map the epitope on this glycoprotein that is involved in neutralization of bovine rotavirus and virus attachment to cells during infection. Sonza et al (1983) and Thiriart et al (1986) also produced neutralizing MAbs against rotavirus, whilst direct detection of rotavirus in porcine faecal specimens was achieved by Liprandi et al (1986), who used their MAb against the 45 kDa group specific antigen in a double sandwich indirect ELISA system.…”
Section: Neonatal Diarrhoeamentioning
confidence: 99%
“…Rotaviruses have been grouped into five antigenically distinct groups (A to E) with group A probably being the most prevalent (Pedley et al, 1986). Group A rotaviruses share a common group antigen (Woode et al, 1976) on protein VP6, an inner capsid protein (Greenberg et al, 1983b). Group A rotaviruses have been further classified into two subgroups (I and II) based on the subgroup antigen also located on VP6 (Greenberg et al, 1983b;Estes et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Group A rotaviruses share a common group antigen (Woode et al, 1976) on protein VP6, an inner capsid protein (Greenberg et al, 1983b). Group A rotaviruses have been further classified into two subgroups (I and II) based on the subgroup antigen also located on VP6 (Greenberg et al, 1983b;Estes et al, 1983). The majority of animal rotaviruses possess the subgroup I antigen while the majority of human rotaviruses have the subgroup II antigen (Hoshino et al, 1984).…”
Section: Introductionmentioning
confidence: 99%